Effectiveness of Baby Powder Locking Technique on Durability of Toraja Fantasy Makeup - Huwaida, Dindaswari Fathiya; Krisnawati, Maria (Universitas Negeri Semarang, 2026)
The ephemeral nature of water-based body painting presents significant technical challenges in tropical climates, particularly regarding durability against perspiration and friction during long duration performances. This study explores a material innovation using a baby powder locking technique to enhance pigment adhesion and achieve a specific matte aesthetic resembling